2003
DOI: 10.1103/physreve.67.021904
|View full text |Cite
|
Sign up to set email alerts
|

Energy resolution and dynamical heterogeneity effects on elastic incoherent neutron scattering from molecular systems

Abstract: Incoherent neutron scattering is widely used to probe picosecond-nanosecond time scale dynamics of molecular systems. In systems of spatially confined atoms the relatively high intensity of elastic incoherent neutron scattering is often used to obtain a first estimate of the dynamics present. For many complex systems, however, experimental elastic scattering is difficult to interpret unambiguously using analytical dynamical models that go beyond the determination of an average mean-square displacement. To circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 25 publications
2
72
0
Order By: Relevance
“…We remark that the neglection of higher order terms in the limit of zero q is the analogue to the wellknown Gaussian approximation that has been applied frequently to extract the apparent MSD. Using the series approximation, we introduce a very general account that can also easily be compared to earlier results on nonGaussian behavior, generally causing deviations in the q 4 term [11]. In experiments, the limit of zero q cannot be reached, and a polynomial fit in q 2 up to order q 4 should be used to obtain u 2 ω [18].…”
Section: The Generalized Mean-squared Displacement U 2 ωmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark that the neglection of higher order terms in the limit of zero q is the analogue to the wellknown Gaussian approximation that has been applied frequently to extract the apparent MSD. Using the series approximation, we introduce a very general account that can also easily be compared to earlier results on nonGaussian behavior, generally causing deviations in the q 4 term [11]. In experiments, the limit of zero q cannot be reached, and a polynomial fit in q 2 up to order q 4 should be used to obtain u 2 ω [18].…”
Section: The Generalized Mean-squared Displacement U 2 ωmentioning
confidence: 99%
“…In the last decade, the physical meaning of the apparent MSD has been explored in several studies on the dependence on the instrumental resolution, from both theoretical [11][12][13][14][15][16] and experimental view points [17]. In a different approach to advance the analysis, the apparent MSD has been explicitly calculated using a dynamical model for the full quasi-elastic spectra, thereby allowing to separate internal from global dynamics during protein denaturation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[33,38] The concept has also been incorporated into the formalism that describes the dynamics accompanying the glass transition in molecular systems. When the protein relaxation time decreases with temperature, as it usually does, it has been shown that measurement of r 2 R over a finite time window can introduce an apparent DT when there is no actual change in the elastic incoherent DSF, S(Q, ω = 0).…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity introduces a correction to fourth order in Q that can be used to extract the variance of the distribution of mean-square displacements. [33,34] Similarly, the global MSD obtained from neutron scattering measurements depends on the energy resolution employed. The MSD is obtained from the elastic (ω = 0) component of the resolution broadened dynamic structure factor (DSF), S R (Q, ω = 0), as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation